Digital Literacy A Comparative Study of Schools - Ilyas, Zeba (JOURNAL OF INDIAN EDUCATION, 2020)
The rapid advances recently made in digitalisation have very important implications for the entire society. Education which is the most powerful tool for the economic, social and cultural development across the globe is also being affected by the use of digital resources. The challenge that confronts our education system today is how the curriculum and the teaching learning process can be transformed in order to provide the learner with skills to function effectively in today’s information rich and continuously changing environment. These days, education is at the confluence of powerful and rapid shifting political, technological and educational forces that would shape structure of educational systems across the world for the remainder of this century. Many countries are involved in rigorous efforts to bring changes in the pedagogical processes in order to prepare the learners information and technology based society. It requires that the learners should make meaningful use of digital knowledge to develop, among themselves a critical skills to achieve long term educational goals. The present study aims to examine the integration of digital resources in to teaching learning by school teachers. The study also compares the knowledge and the use of digital resources by government and private school teachers. A sample of 200 teachers was selected from these schools in Delhi. Two checklists of software and hardware were developed and the responses of teachers were analysed qualitatively using percentage. The findings reveal that the awareness of government and private school teachers about the software and hardware used in teaching is satisfactory barring few of these digital resources.